Injectable antibacterial Ag-HA/ GelMA hydrogel for bone tissue engineering - Wang, Jiapu; Wang, Xuefeng; Liang, Ziwei; Lan, Weiwei; Wei, Yan; Hu, Yinchun; Wang, Longfei; Lei, Qi; Huang, Di (Frontiers in Bioengineering and Biotechnology, 2023)
Background: Fracture or bone defect caused by accidental trauma or disease is a growing medical problem that threats to human health.Currently, most orthopedic implant materials must be removed via follow-up surgery, which requires a lengthy recovery period and may result in bacterial infection. Building bone tissue engineering scaffolds with hydrogel as a an efficient therapeutic strategy has outstanding bionic efficiency.By combining some bionic inorganic particles and hydrogels to imitate the organic-inorganic characteristics of natural bone extracellular matrix, developing injectable multifunctional hydrogels with bone tissue repair effects and also displaying excellent antibacterial activity possesses attractive advantages in the field of minimally invasive therapy in clinical. Methods: In the present work, a multifunctional injectable hydrogel formed by photocrosslinking was developed by introducing hydroxyapatite (HA) microspheres to Gelatin Methacryloyl (GelMA) hydrogel. Results: The composite hydrogels exhibited good adhesion and bending resistance properties due to the existence of HA. In addition, when the concentration of GelMA is 10% and the concentration of HA microspheres is 3%, HA/GelMA hydrogel system displayed increased microstructure stability, lower swelling rate, increased viscosity, and improved mechanical properties. Furthermore, the Ag-HA/GelMA demonstrated good antibacterial activity against Staphylococcus aureus and Escherichia coli, which could signifificantly lower the risk of bacterial infection following implantation. According to cell experiment, the Ag-HA/GelMA hydrogel is capable of cytocompatibility and has low toxicity to MC3T3 cell. Conclusion: Therefore, the new photothermal injectable antibacterial hydrogel materials proposed in this study will provide a promising clinical bone repair strategy and is expected to as a minimally invasive treatment biomaterial in bone repair fields.